Pricing Mobility: Experiences in the Netherlands - Rietveld, Piet (European Journal of Transport and Infrastructure Research, 2001)
Externalities of transport do not only depend on the number of kilometres driven, but also on factors such as road type, time of day, car type and on driving behaviour such as speed and acceleration. The present pricing system of car use and ownership in the Netherlands is such that the degree of differentiation is small, except for the car type aspect. Thus there is a clear mismatch between the differentiation in external costs and in pricing. A considerable share (55%) of all car-related taxes in the Netherlands relates to car ownership. The rest (45%) is paid for car use. The structure of the tax system is only vaguely related to the differentiation in the external effects. To overcome this problem, variabilisation of the tax system has been a main objective during the past 20 years in the Netherlands. A discussion is given of various ways to achieve this variabilisation such as a spatial graduation of fuel taxes, congestion pricing, a kilometre charge, and paid parking. The treatment of transport costs as a deductible in the income tax leads to major distortions in the Netherlands: a low variable cost for commuting, a zero variable cost for the company car, and a negative cost in the case of private car use for business purposes. Thus, two major problems in the taxation of road transport are found: lack of differentiation so that the tariffs do not reflect the external costs, and adverse effects of the structure of the income tax in the fields of business traffic and commuting leading to low, zero or even negative costs of car use. Discussions on the reform of transport-related taxes generally focus on the first problem but the figures presented in this study indicate that the second problem also deserves high priority.